RIBA ALAT TRANSAKSI KEUANGAN YANG MEMISKINKAN DILIHAT DARI SUDUT PANDANG EKONOMI ISLAM DAN EKONOMI KRISTEN - Tuti Supatminingsih; Syamsu Rijal; Jasmin; Muhammad Ardi; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
Usury has become the main driving force in the conventional financial system in most countries, especially Western countries, and even countries that implement dual financial systems are not left behind. This research seeks to examine usury and why usury must be removed from financial transactions. The study revealed that no religion justifies usury in any form and concluded that continuous consumption of usury will impoverish the world economy and even the welfare of citizens will not be left behind because it is a tool that does not function in increasing utility.